Sour cherry for fresh consumption in the retail sector A consumer aspect - Felföldi, J.; Apáti, F. (International Journal of Horticultural Science, 2010)
The basic objective of our study is the promotion of fresh consumption of sour cherry and the enhancement of necessary knowledge. Primer collection of data was planned in three groups of retail shops, always sour cherry being the matter of study. The sampling dates were adapted to the sour cherry season weeks in Hungary. Three samples per week have been taken. Every time a short interview and purchase was planned. Every time, it was stated that the commodity was held for a longer period on the shelf, which trespasses the optimum of the fruit. At the same time there was no concordance between quality and price. From the point of view of the consumer this cannot be accepted.